Crotalphine attenuates pain and neuroinflammation induced by experimental autoimmune encephalomyelitis in mice - Giardini, Aline C.; Evangelista, Bianca G.; Sant’anna, Morena B.; Martins, Barbara B.; Lancellotti, Carmen L. P.; Ciena, Adriano P. [UNESP]; Chacur, Marucia; Pagano, Rosana L.; Ribeiro, Orlando G.; Zambelli, Vanessa O.; Picolo, Gisele (My University, 2021)
Multiple sclerosis (MS) is a demyelinating disease of inflammatory and autoimmune origin, which induces sensory and progressive motor impairments, including pain. Cells of the immune system actively participate in the pathogenesis and progression of MS by inducing neuroinflamma-tion, tissue damage, and demyelination. Crotalphine (CRO), a structural analogue to a peptide firstly identified in Crotalus durissus terrificus snake venom, induces analgesia by endogenous opioid release and type 2 cannabinoid receptor (CB2) activation. Since CB2 activation downregulates neuroinflam-mation and ameliorates symptoms in mice models of MS, it was presently investigated whether CRO has a beneficial effect in the experimental autoimmune encephalomyelitis (EAE). CRO was administered on the 5th day after immunization, in a single dose, or five doses starting at the peak of disease. CRO partially reverted EAE-induced mechanical hyperalgesia and decreased the severity of the clinical signs. In addition, CRO decreases the inflammatory infiltrate and glial cells activation followed by TNF-α and IL-17 downregulation in the spinal cord. Peripherally, CRO recovers the EAE-induced impairment in myelin thickness in the sciatic nerve. Therefore, CRO interferes with central and peripheral neuroinflammation, opening perspectives to MS control.
Keywords: Glial cells; IL-17; Inflammation; Neurodegeneration; Neurodegenerative disease